Dinamika Public Relations Pemerintah dan Framing Media dalam Merespons Anomali Ekonomi Triwulan I 2026: Pertumbuhan Ekonomi di Tengah Pelemahan Rupiah terhadap Dolar AS (Indo-MathEdu Intellectuals Journal, 2026)
The first quarter of 2026 reflected a relatively contradictory economic condition in Indonesia. Amid ongoing national economic growth, the rupiah continued to weaken against the US dollar. This situation generated various public responses, particularly within digital media, which has become the primary space for people to access and discuss economic information. Media coverage regarding the weakening rupiah, market conditions, and global economic uncertainty influenced public perceptions of national economic stability and the government’s performance. In this context, government public relations faced increasingly complex challenges. The government was not only required to deliver economic information quickly and accurately, but also to maintain public trust amid the massive flow of information and diverse opinions circulating in digital media. The discrepancy between economic growth data and the realities experienced by parts of society also had the potential to create confusion, social anxiety, and economic speculation in the public sphere. This study employed a qualitative approach using a literature review method based on digital news articles, journals, books, and previous studies. The research aims to analyze how the media framed the economic anomaly in the first quarter of 2026 and to examine the dynamics of Indonesian government public relations in responding to these conditions through public communication strategies in the digital era.